Adaptive Leadership 5.0: Integrasi Agile Mindset, Growth Mindset, dan Artificial Intelligence di Tengah Disrupsi Vuca - Rendy Mahardika; Aurel Diyah Agustin (Lembaga Pengembangan Kinerja Dosen, 2025)
The VUCA era (Volatility, Uncertainty, Complexity, Ambiguity) demands organizations to adapt rapidly, effectively, and intelligently. Traditional leadership models often prove inadequate to respond to such complexities. This study explores Adaptive Leadership 5.0, a modern leadership paradigm that integrates the Agile Mindset, Growth Mindset, and Artificial Intelligence (AI) as foundational pillars to navigate disruption. Agile Mindset enables a culture of experimentation and continuous learning, while Growth Mindset provides the psychological foundation for resilience and innovation. Meanwhile, AI acts as a catalyst for data-driven decision-making and managerial efficiency. This study investigates how the synergy of these three elements enhances critical thinking, complex problem solving, and adaptive managerial competencies. Through a conceptual approach and literature review, this research confirms that Adaptive Leadership 5.0 strengthens leaders’ capabilities to thrive amidst uncertainty and rapid change in the VUCA environment.